Optimasi Breakfast Meal Flakes Berbasis Tepung Jali Termodifikasi - Rahmawati, Lufi Karisma; Muhandri, Tjahja; Iwansyah, Ade Chandra; Palupi, Nurheni Sri; Ambarwati, Karsi (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2025)
Jali (Coix lacryma-jobi L.) is a promising food crop in Indonesia, but its contribution to food security needs more improvement. This research aimed to analyze physico-chemical characteristics of native jali flour and its modified flour after treated by heat moisture treatment (HMT) and autoclaving-cooling (AC) method, and finally observe their effects on breakfast meal flakes (BMF). Both native and treated flour were analyzed for degree of whiteness, swelling power, solubility, water absorption index (WAI), water holding capacity (WHC), and gelatinization profile. HMT-modified jali flour exhibited solubility of 7.77%, gelatinization temperature of 74.95 °C, and peak viscosity of 3255 cP while amylose and resistant starch content reached 20.50% and 6.27%, respectively. Meanwhile, AC-modified jali flour showed lower solubility (4.13%), higher gelatinization temperature (76.15 °C), peak viscosity of 3220 cP, with amylose content of 22.30% and significantly higher resistant starch content (13.93%). Due to its superior resistant starch content, AC-modified Jali flour was selected for BMF formulation. The formulation was optimized through D-optimal with independent variables of 50−100% jali flour and 0−50% sorghum flour. As a result, the optimum formulation was obtained with a desirability value of 0.713, consisted of 100% jali flour without added sorghum flour. The optimized BMF had resistant starch 11.46%, rehydration capacity 58.48%, and hardness 415.12 gf. The product has the potential to diversify healthy breakfast options for community and may contribute to diabetes prevention.